Impairment of muscular endothelial cell regeneration in dermatomyositis - Lemmer, D.; Schmidt, J.; Kummer, K.; Lemmer, B.; Wrede, A.; Seitz, C.; Balcarek, P.; Schwarze, K.; Müller, G. A.; Patschan, D.; Patschan, S. (Frontiers in Neurology, 2022)
Background and aim Inflammatory myopathies are heterogeneous in terms of etiology, (immuno)pathology, and clinical findings. Endothelial cell injury, as it occurs in DM, is a common feature of numerous inflammatory and non-inflammatory vascular diseases. Vascular regeneration is mediated by both local and blood-derived mechanisms, such as the mobilization and activation of so-called proangiogenic cells (PACs) or early endothelial progenitor cells (eEPCs). The current study aimed to evaluate parameters of eEPC integrity in dermatomyositis (DM), compared to necrotizing myopathy (NM) and to non-myopathic controls. Methods Blood samples from DM and NM patients were compared to non-myositis controls and analyzed for the following parameters: circulating CD133+/VEGFR-2+ cells, number of colony-forming unit endothelial cells (CFU-ECs), concentrations of angiopoietin 1, vascular endothelial growth factor (VEGF), and CXCL-16. Muscle biopsies from DM and NM subjects underwent immunofluorescence analysis for CXCR6, nestin, and CD31 (PECAM-1). Finally, myotubes, derived from healthy donors, were stimulated with serum samples from DM and NM patients, subsequently followed by RT-PCR for the following candidates: IL-1β, IL-6, nestin, and CD31. Results Seventeen (17) DM patients, 7 NM patients, and 40 non-myositis controls were included. CD133+/VEGFR-2+ cells did not differ between the groups. Both DM and NM patients showed lower CFU-ECs than controls. In DM, intramuscular CD31 abundances were significantly reduced, which indicated vascular rarefaction. Muscular CXCR6 was elevated in both diseases. Circulating CXCL-16 was higher in DM and NM in contrast, compared to controls. Serum from patients with DM but not NM induced a profound upregulation of mRNS expression of CD31 and IL-6 in cultured myotubes. Conclusion Our study demonstrates the loss of intramuscular microvessels in DM, accompanied by endothelial activation in DM and NM. Vascular regeneration was impaired in DM and NM. The findings suggest a role for inflammation-associated vascular damage in the pathogenesis of DM.